Diversification and division - 'academic drift' in Swedish teacher education in the aesthetic school subjects in a new higher education structure - Erixon, Per-Olof; Jeansson, Åsa; Westerlund, Stina; Wikberg, Stina (Education Inquiry, 2025)
This study deals with the academisation or "academic drift" of teacher education in the aesthetic subjects in Sweden from the 1970s to the millennium shift. After long preparations that already began after the Second World War, TE, along with other vocational education, was integrated into the Swedish university system as part of the expansion of the higher education sector in 1977 (H77). The study's aims were to describe and analyse how the conditions for teacher education in practical/aesthetic subjects changed in the new and diversified higher education sector. For the study, we drew on Official Reports of the Swedish Government (SOU), a type of authoritative policy text intended to influence an activity, but which govern less formally than "governing policy texts" like bills that are legislative in nature. Our study reveals that a division was made between the old, prestigious and discipline-based universities and the newcomers in terms of vocationally-based education. The entire teacher education ended up on the periphery of the new higher education sector. We establish that the absence of own academic structures and thereby power within the higher education structures has harmed the independent development of teacher education in the aesthetic subjects as part of the enlarged higher education sector in the process of them moving from school subjects to university-like disciplines.